Interplay between multipolar order and multipole-induced superconductivity in PrTi2Al20 - Akito Sakai; Yosuke Matsumoto; Mingxuan Fu; Takachika Isomae; Masaki Tsujimoto; Eoin O’Farrell; Daisuke Nishio-Hamane; Satoru Nakatsuji (Nature Communications)
Abstract Multipolar moments entail a new route to tackle frontier problems in superconductivity (SC). A key progress in the search for multipolar SC is the discovery of PrT r 2Al20 (T r = Ti, V), which possesses quadrupolar and octupolar but no magnetic dipolar moments. The Kondo entanglement of these multipolar moments with conduction electrons leads to exotic SC within the multipolar ordered phase, though the precise nature of the SC remains unexplored. We experimentally investigate the SC gap structure of SC in PrTi2Al20 and its La-doping evolution. Our results indicate deviations from a single s-wave gap, instead favoring nodal d-wave or multiple gaps. While the SC is robust against La dilution, the SC gap structure changes with minimal La doping, coinciding with a sharp change in the ferroquadrupolar (FQ) order. This suggests an intimate link between the quadrupolar order parameter and SC pairing, providing insight into the coexistence of SC with multipolar order.